A game-based approach to the teaching of object-oriented programming languages - Rodríguez Corral, José María; Civit Balcells, Antón; Morgado Estévez, Arturo; Jiménez Moreno, Gabriel; Ferreiro Ramos, María José (Computers and education, 2014)
Students often have difficulties when trying to understand the concepts of object-oriented programming (OOP). This paper presents a contribution to the teaching of OOP languages through a game-oriented approach based on the interaction with tangible user interfaces (TUIs). The use of a specific type of commercial distributed TUI (Sifteo cubes), in which several small physical devices have sensing, wireless communication and user-directed output capabilities, is applied to the teaching of the C# programming language, since the operation of these devices can be controlled by user programs written in C#. For our experiment, we selected a sample of students with a sufficient knowledge about procedural programming, which was divided into two groups: The first one had a standard introductory C# course, whereas the second one had an experimental C# course that included, in addition to the contents of the previous one, two demonstration programs that illustrated some OOP basic concepts using the TUI features. Finally, both groups completed two tests: a multiple-choice exam for evaluating the acquisition of basic OOP concepts and a C# programming exercise. The analysis of the results from the tests indicates that the group of students that attended the course including the TUI demos showed a higher interest level (i.e. they felt more motivated) during the course exposition than the one that attended the standard introductory C# course. Furthermore, the students from the experimental group achieved an overall better mark. Therefore, we can conclude that the technological contribution of Sifteo cubes – used as a distributed TUI by which OOP basic concepts are represented in a tangible and a visible way – to the teaching of the C# language has a positive influence on the learning of this language and such basic concepts. •We present a game-based approach to the teaching of object-oriented languages.•Such approach is based on the interaction with a tangible user interface (TUI).•This TUI represents object-oriented programming (OOP) concepts in a visible form.•The analysis of C# demos to control the TUI makes the study of OOP concepts easier.•Pupils who took C# classes including such demos got better results in the experiments.